Heat Transfer in An Array of Staggered Tube Using CFD Method - Azraai, Shamsul Bahari; Sulaiman, Mohd Yusoff; Din, Abdul Talib; Mohlis, Mohd Adib Muizzuddin (Penerbit Unimap, 2009)
Heat exchangers are found in numerous industrial applications such as steam generation in aboller or cooling in the coll of an air conditioner. Heat tranfer in flow across tube bank is importance in designing of heat exchanger. there are two types of arrangement of tube banks, such as in-kine and staggered maner and are characterized by the dimensionless transverse and longitudinal pitches. CFD simulation codes ANSYS CFX software is used to investigated the heat flow across an array of staggered tuibe at three different aspect pitch ratios. The working fluids used are air and water. The flow and beat transfer characteristic of a staggered tube a nearly the same of a single cylinde/tube. The first row characteristic is usually the same as a single tube. But for the second row and so on, the cherectieristic are depend on the rows that's come first. for a single tube actually there are two boundry layers which occur at front of the tube and the back of the tube. laminar boundry layer alwas developed at the front while turbulent at the back. Several geometry. The other parameters such as the flud velocity and temperature are also defined accoding to the previous research. With these parameters th 3-D simulation has been done using CFX software. The results obtained are in terms of velocity, temperature and pressure profile. From the investigation, the lower value of potch ratio is found to give better heat tranfer rate. When the pitch value is decreased, the pressure drop will rise and thus will increace the heat transfer rate.